Case report: pulmonary artery perforation during transseptal puncture for left atrial appendage closure requires emergency cardiac operation - Wang, Yue; Song, Beibei; Liu, Bing; Zhang, Hui; Bi, Chenglong; Liu, Wenhao; Ma, Gang; Li, Bo (Frontiers in Cardiovascular Medicine, 2023)
Patients with atrial fibrillation who take a high bleeding risk and are not candidates for oral anticoagulation therapy are increasingly being referred for left atrial appendage closure (LAAC) as an alternative method of stroke prevention. However, certain manipulations performed during the LAAC procedure, such as transseptal puncture (TSP), may potentially result in vessel injury and lead to cardiac tamponade or even fatality. Clinical significance and management strategies associated with these complications remain controversial. A 74-year-old female patient with atrial fibrillation was referred for left atrial appendage occlusion. During the puncture of the atrial septum, the catheter sheath inadvertently exited through the roof of the right atrium and continued to advance, resulting in pulmonary artery perforation. The patient underwent immediate pericardiocentesis and drainage, followed by surgical exploration for suturing the tear in the pulmonary artery and ligation of the left atrial appendage. This represents the first reported case of a pulmonary artery perforation occurring during a transseptal puncture procedure for left atrial appendage closure. The case exemplifies the feasibility of emergency cardiac surgery as a therapeutic intervention.